The genus Taphaeus Wesmael, 1835 (Hymenoptera: Braconidae: Helconinae) from China with description of a new species - Yan, Cheng-Jin; Achterberg, Van; Chen, Xue-Xin (Zootaxa, 2012)
The genus Taphaeus Wesmael, 1835 (Hymenoptera: Braconidae: Helconinae) is reported for the first time from China. A new species of this genus, Taphaeus pseudohiator Yan, van Achterberg et Chen, sp. n., is described and illustrated. A key to the Palaearctic species of this genus is updated to include the new species.